Licensing unergative objects in ergative languages: The view from Polynesian. (20th May 2022) - Tollan, Rebecca; Massam, Diane
Abstract: Transitive and unergative verbs have long received a uniform syntactic analysis, where they differ in whether an overt object is present (in transitives) or absent (in unergatives). We examine how objects of unergative verbs are case licensed when they are present, focusing on a contrast between two related Polynesian languages: Samoan and Niuean. Both languages have ergative case systems, with subjects of intransitive verbs receiving absolutive case. When unergatives have an overt object, however, a difference emerges. In Samoan, ergative case is absent: the subject of a transitivized unergative is absolutive, and the object receives "middle case." In Niuean, the resulting transitive exhibits an ergative–absolutive frame. Working within a split‐vP system, we propose that the contrast between Samoan and Niuean results from the interaction of three parametric differences. This comparative analysis highlights the importance of considering unergative constructions when determining the underlying syntax of any given case system.